PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS KONSTRUKTIVISME PADA POKOK BAHASAN IKATAN KIMIA KELAS X SMA/MA - Fitria Purnama Sari; Johni Azmi; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research has been to produce LKPD based on Construktivisme on the subject of chemical bonds valid based on feasibility of content, language, presentation and grapic. The research was conducted in Chemistry Education Department of PMIPA FKIP University of Riau on August-december, 2018. Research is done by research and development research and development (R & D) with 4-D model, because time and cost limitation is only done until development stage. Instrument of data collecting in this research is validation sheet and teacher response questionnaire as well as questionnaire response of learners. LKPD that has been developed validated by 3 validators it’s 2 namely lecturer of Chemistry Education FKIP UR and 1 namely lecturer of Chemistry Education FKIP UIN Suska Riau , then tested to 15 students in SMA Negeri 2 Pekanbaru and 15 students in SMA Negeri 12 Pekanbaru. The average scores of validation of feasibility aspects of content, language, presentation and kegrafisan of LKPD developed respectively were 98,86%, 91,67%, 95,83%, and 90,63% with an overall average of 94,52% (valid). The mean outcome of the teacher's response questionnaire to LKPD was 90,62(good), the average score of the limited trials conducted in 2 schools were 90,26 %(good) and 93,33%(good) respectively.Key Words: Development, LKPD, construktivisme, chemical bonds